A Critical Review of Performance Improvement Techniques in Compression Ignition Engines - Cahya Wahyu Pribadi, Elwas; Rachmat Subagyo,; Abdul Ghofur,; Rizky Chandra Ariesta, (International Journal of Marine Engineering Innovation and Research, 2025)
Compression ignition engines play a critical role in various industrial and transportation applications; however, their environmental impact remains a major concern. Continuous research efforts have been directed toward optimizing engine performance to enhance efficiency and reduce emissions. This paper reviews key strategies that have been investigated for performance optimization, primarily focusing on combustion chamber geometry, fuel properties, and advanced combustion modes. Each of these factors significantly influences the combustion process, thereby affecting engine performance and emission characteristics. While no single method has proven sufficient to fully resolve all challenges associated with these engines, combustion chamber geometry optimization has demonstrated potential in improving efficiency and reducing pollutant emissions. More notably, integrating multiple optimization techniques appears to offer a more effective pathway toward achieving substantial improvements in overall engine performance.